Screen Time, Habit Formation, and Self-Regulation in Primary School Children: A Literature-Based Educational Analysis Through Plato - Abner, Dwight; Prihatina, Ni Putu Indah Cahya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The widespread use of smartphones, tablets, and video games in childhood has intensified concern over their effects on children’s behavior, emotional regulation, attention, and social development. For primary school children, this issue extends beyond health because digital habits also shape learning readiness, self-control, classroom participation, and family routines that support schooling. This study examines how Plato’s account of moral formation in The Republic can help interpret contemporary research on children’s gadget and video game use. Using a qualitative literature-based approach, the study analyzes Plato’s educational thought together with peer-reviewed studies and policy documents on screen time, parenting, self-regulation, sleep, attention, and child development. The analysis draws on purposively selected literature and thematic synthesis. Five major patterns were identified: screen environments can function as habit-forming settings; excessive use is associated with socioemotional and behavioral difficulties; screen use may displace sleep and sustained attention; self-regulation in childhood depends heavily on adult mediation; and balanced guidance is more educationally productive than either permissiveness or punitive prohibition. The study offers an education-centered framework for understanding digital media use in primary school contexts and argues that the central issue lies not in technology itself, but in the quality of guidance, routine, and moral formation surrounding its use.